Optimalisasi Pengetahuan Siswa Terhadap Bahaya Penyakit Menular TB Melalui Media Inovasi Vidio Edukasi Peduli TB - Mizam Ari Kurniyanti; Alya Arrifda; Wilma Ardila Putri; Najma Nafisah (I-Com: Indonesian Community Journal, 2025)
TBC is an infectious disease that spreads through droplets, and the incidence rate increases in adolescence due to high mobility. One of the preventions that can be done for the spread of TBC is to provide health education in the form of educational videos on TBC Care to students so that knowledge related to the prevention and transmission of TBC can be prevented. The purpose of this community service activity is to increase the knowledge of SMKN 12 students about TBC through the provision of Peduli TBC educational videos and the provision of leaflets and posters related to TBC. The method used is in the form of screening the Peduli TBC educational video. The results of the activity were an increase in knowledge of SMKN 12 students after being given educational videos